The Impact of Soil Conditioners on Some Chemical Properties of Soil and Grain Yield of Corn (Zea Mays L.) - Melis Cercioglu (Journal of Agricultural Sciences)
The goal of this study was to explore the effects of various soil conditioners on selected properties (pH; organic matter, OM; electrical conductivity, EC; cation exchange capacity, CEC) of a Xerofluvent soil and corn yield. During the experiment, four amendments were applied in an experimental set of plots: tobacco waste compost (TWC), poultry manure (PM), bio-humus (BH), and chemical fertilizer (NPK). Soils were treated with TWC at the rate 50 t ha-1, PM at the rate 4 t ha-1, BH at the rate 10 t ha-1 and NPK at the rate 300 kg ha-1, respectively. All organic conditioners were increased soil pH, OM, CEC, EC and corn yield when compared with the control soil and these parameters have been changed from 5.7% to 333%. The most effective soil conditioners were determined as tobacco waste compost, biohumus, and poultry manure. The findings of current study suggest that 50 t ha-1 TWC should be added to soil as a priority for improving properties of a Typic Xerofluvent soil and crop yield.